The prognostic value of diagnosing concurrent multiple myeloma in immunoglobulin light chain amyloidosis. (23rd February 2013) - Dinner, Shira; Witteles, Wesley; Witteles, Ronald; Lam, Anthony; Arai, Sally; Lafayette, Richard; George, Tracy I.; Schrier, Stanley L.; Liedtke, Michaela
Summary The prevalence and prognostic value of a concomitant diagnosis of symptomatic or asymptomatic multiple myeloma (MM), as defined by the current International Myeloma Working Group (IMWG) criteria, in patients with immunoglobulin light chain amyloidosis (AL), are unknown. We studied 46 consecutive patients with AL who underwent quantification of serum M‐protein and clonal bone marrow plasma cells, as well as a comprehensive evaluation for end organ damage by MM. Using standard morphology and CD138 immunohistochemical staining, 57% and 80% of patients were found to have concomitant MM, respectively. Nine patients exhibited end organ damage consistent with a diagnosis of symptomatic MM. While overall survival was similar between AL patients with or without concurrent myeloma (1‐year overall survival 68% vs. 87%; P = 0·27), a diagnosis of symptomatic myeloma was associated with inferior outcome (1‐year overall survival 39% vs. 81%; P = 0·005). Quantification of bone marrow plasma cells by both standard morphology and CD138 immunohistochemistry identified a much higher prevalence of concurrent MM in patients with AL than previously reported. Evaluation of bone marrow plasma cell infiltration and presence of myeloma associated end organ damage could be clinically useful for prognostication of patients with AL.